Sikap Bahasa Mahasiswa terhadap Penggunaan Bahasa Inggris di Universitas Muhammadiyah Bone: Penelitian - Taslim Taslim; Nursakina Nursakina; Nadia Vega; Satriani Satriani; Sulistiawati Sulistiawati; Kahadijah Kahadijah; Andi Athika Magfirah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to analyze the language attitudes of Muhammadiyah Bone University students towards the use of English in the campus environment. With a quantitative approach through distributing questionnaires, data was collected from students of the English Language Education Department. The research results show that the majority of students have a positive attitude towards English, which is reflected in the cognitive, affective and conative components. This finding is in line with previous research conducted at various universities, such as Diponegoro University, Muhammadiyah University Gresik, and Manado State University, which also confirmed that a positive attitude plays an important role in supporting English language mastery. The implications of this research can be the basis for developing bilingual policies on campus as well as improving supporting facilities such as language laboratories.